2015
DOI: 10.1039/c5tc02025e
|View full text |Cite
|
Sign up to set email alerts
|

Compositions and thermoelectric properties of XNiSn (X = Ti, Zr, Hf) half-Heusler alloys

Abstract: Rietveld analysis of neutron powder diffraction data has been used to investigate the compositions of XNiSn (X = Ti, Zr, Hf) half-Heusler alloys prepared by solid state reactions. All samples containing Ti have 2-3% excess Ni, whereas the samples with X = Zr, Hf are almost stoichiometric.Samples with mixed X-metals are characterised by the presence of 3-4 distinct X 1-x X' x Ni 1+y Sn half-Heusler phases. Variable temperature and time dependent neutron powder diffraction for X = Ti and X = Ti 0.5 Hf 0.5 demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 49 publications
9
37
1
Order By: Relevance
“…The substitution of Ti by Hf and Zr elements to form (Ti, Hf, and Zr)NiSn alloys is conrmed to be an effective way to enhance the thermoelectric properties of TiNiSn. [45][46][47][48][49][50][51] Herein, we investigate the effect of a mixture of Ti, Hf, and Zr on the ideal strength of (Ti, Hf, and Zr)NiSn. The most plausible slip system (111)/h 110i is chosen to impose the shear deformation on the doped systems (72 total atoms) of Ti 0.5 Hf 0.5 NiSn, Ti 0.5 Zr 0.5 NiSn, Ti 0.5 Hf 0.25 Zr 0.25 NiSn, and Hf 0.5 Zr 0.5 NiSn, respectively.…”
Section: Effect Of Doping Of Tinisn On Mechanical Propertiesmentioning
confidence: 99%
“…The substitution of Ti by Hf and Zr elements to form (Ti, Hf, and Zr)NiSn alloys is conrmed to be an effective way to enhance the thermoelectric properties of TiNiSn. [45][46][47][48][49][50][51] Herein, we investigate the effect of a mixture of Ti, Hf, and Zr on the ideal strength of (Ti, Hf, and Zr)NiSn. The most plausible slip system (111)/h 110i is chosen to impose the shear deformation on the doped systems (72 total atoms) of Ti 0.5 Hf 0.5 NiSn, Ti 0.5 Zr 0.5 NiSn, Ti 0.5 Hf 0.25 Zr 0.25 NiSn, and Hf 0.5 Zr 0.5 NiSn, respectively.…”
Section: Effect Of Doping Of Tinisn On Mechanical Propertiesmentioning
confidence: 99%
“…17 Other successful routes are to enhance boundary scattering through reduction of the average grain size [18][19][20] and by exploiting out-of-equilibrium approaches and segregation to create nanostructured materials. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] We have demonstrated that TiNiSn is unique in its ability to accommodate signicant amounts of interstitial Ni and Cu metals ($10% site occupancy), [41][42][43][44] whereas ZrNiSn and HfNiSn have far lower capacities (<2-3%) under the same preparation conditions. 45 These interstitials form highly effective phonon scattering centres, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Half-Heusler compounds with 18 valence electron count (VEC) per unit cell have been widely studied as one of the promising thermoelectric materials working in the middle temperature range due to their narrow bandgap and high Seebeck coefficients, such as MCoSb, MNiSn (M = Ti, Zr, Nb, and Hf), et al [10][11][12][13][14] Among these compounds with 18 VEC, MCoSb based half-Heusler compounds (M = Ti, Zr, Nb, and Hf) have been extensively investigated including the substituting at M, A or B sites and many studies have achieved high thermoelectric properties. Yuan et al synthesized the ZrCoSb 1−x Sn x by substituting Sn on Sb sites and the maximum ZT value of 0.52 at 973 K was obtained [15].…”
Section: Introductionmentioning
confidence: 99%